Education About Clean and Healthy Behavior Regarding CTPS at Schools in Class 3 SDN 1 Ciparanti - Julianti, Adliana; Qolbi, Almi Nurul; Nur D, Deva; Gunawan, Gungun; P, Hanna Amelia; Mubarok, Helmi; Pramudya, M Ikhsan; Rafli, Muhammad; Nabil, Putri; Rachmawati, Salma; Rahmah, Shofia; Novia, Sri; Septiani, Widya; Anggarasari, Nandhini Hudha; Liza Ghazali, Puspa; Pratiwi, Anggia Suci; Hendrawan, Budi; Mujiarto, Mujiarto (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Clean and healthy behavior in Indonesia known as perilaku hidup bersih dan sehat (PHBS). PHBS in school children is very good for educating and instilling awareness of the importance of cleanliness as an effort to maintain personal and environmental health, especially during the Covid-19 Pandemic encouraging children to carry out a Clean and Healthy Lifestyle. This is one of the PKM Programs. The purpose of this study is to obtain an overview of PHBS in students of SDN Ciparanti 1. The method used is descriptive method. With a sample of 20 people from all 3 classes. The results showed that the behavior of respondents who did handwashing with soap was always carried out by 40.99%. Suggestions for school residents, especially teachers and community employees around the school as well as parents of students, should make more efforts to understand the importance of the PHBS program in schools and provide understanding to students. Because washing hands with good soap is the most important thing in preventing the spread of viruses and germs. Because 98% of the spread of germs in the body comes from the hands.